2014
DOI: 10.1123/jis.7.1.64
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Transformational Leadership, Leader Effectiveness, and Turnover Intentions: Do Subordinate Gender Differences Exist?

Abstract: The aim of this study was to examine gender differences among subordinates in the strength of relationships between transformational leadership, leader effectiveness, and voluntary organizational turnover intentions. The authors drew from various theoretical bases, including transformational leadership theory, social role theory, and role congruity theory, to undergird the research. National Collegiate Athletic Association (NCAA) Division I male and female assistant coaches of women's basketball, softball, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(121 reference statements)
0
5
1
Order By: Relevance
“…Other research work has often framed this issue from an individual perspective when citing the high turnover within the numbers of women coaches or women's higher intentions to leave the profession Sagas et al, 2006;Narcotta et al, 2007;Wells et al, 2014). However, the present study contends that women coaches' dissatisfaction with their working conditions or possible intentions to leave is a social problem rooted in the organisational gendered practices of high performance sport which prevents women coaches from having meaningful control over their lives (Coakley, 1992;Bruening and Dixon, 2007).…”
Section: Feel a Bit Saturated To Be Honest At The Moment Because I contrasting
confidence: 50%
See 1 more Smart Citation
“…Other research work has often framed this issue from an individual perspective when citing the high turnover within the numbers of women coaches or women's higher intentions to leave the profession Sagas et al, 2006;Narcotta et al, 2007;Wells et al, 2014). However, the present study contends that women coaches' dissatisfaction with their working conditions or possible intentions to leave is a social problem rooted in the organisational gendered practices of high performance sport which prevents women coaches from having meaningful control over their lives (Coakley, 1992;Bruening and Dixon, 2007).…”
Section: Feel a Bit Saturated To Be Honest At The Moment Because I contrasting
confidence: 50%
“…Supportive, positive and healthy workplaces foster effective relationships and so a sign of a healthy workplace is not just trust and respect as previously discussed, but appropriate workloads and resources (Lowe et al, 2003). Other research has often framed this issue from an individual perspective when citing the high turnover within the numbers of women coaches or women’s higher intentions to leave the profession (Cunningham et al, 2003; Cunningham and Sagas, 2003; Narcotta et al, 2007; Sagas et al, 2006; Wells et al, 2014). However, the present study contends that women coaches’ dissatisfaction with their working conditions or possible intentions to leave is a social problem rooted in the organisational gendered practices of high performance sport which prevents women coaches from having meaningful control over their lives (Bruening and Dixon, 2007; Coakley, 1992).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…21 For example, Chelladurai 21 claims that since sports organizations nowadays are in an increasingly dynamic environment, they constantly face contextual issues (e.g., diversity, ethics, league changes, and gender issues) that require transformational leadership. Indeed, several empirical studies have found that athletic directors’ transformational leadership style was positively associated with followers’ satisfaction with leaders, 22 job satisfaction, 23 perceived leadership effectiveness, 24 and decreased turnover intention. 25…”
Section: Literature Reviewmentioning
confidence: 99%
“…26 This model describes the influence of gender on the relationship between leader behaviours and follower outcomes. For instance, Cronin and colleagues 27 found male athletes to perceive greater levels of coach transformational leadership, whereas Vella et al 14 and Wells et al 28 did not find gender differences in perceptions. Similarly, and based on the 3Cs, Jowett and Don Carolis 29 found girls to perceive better quality relations with their coaches than their male counterparts.…”
mentioning
confidence: 99%